2013
DOI: 10.1037/a0032848
|View full text |Cite
|
Sign up to set email alerts
|

Can habituation of sexual responses be elicited in men and women when attention is maintained?

Abstract: Queen's University at KingstonStudies investigating men and women separately suggest a sex difference in the habituation of genital responses to sexual stimuli: Men's responses habituate readily whereas women's responses appear more resistant. These studies also demonstrate that attention is positively correlated with habituation effects when they occur. The preparation hypothesis asserts that women's genital responses occur automatically in the presence of sexual cues to protect them from injuries that may oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…When men and women are shown the same sexual stimuli over and over again, they both report feeling less sexually aroused and devices placed on their genitals also show that they are, in fact, less aroused (Dawson et al 2013;Koukounas and Over 1993;Meuwissen and Over 1990). Simply put, sexy material that once was arousing becomes considerably less arousing over time.…”
Section: Orgasms In Long-term Relationshipsmentioning
confidence: 88%
See 1 more Smart Citation
“…When men and women are shown the same sexual stimuli over and over again, they both report feeling less sexually aroused and devices placed on their genitals also show that they are, in fact, less aroused (Dawson et al 2013;Koukounas and Over 1993;Meuwissen and Over 1990). Simply put, sexy material that once was arousing becomes considerably less arousing over time.…”
Section: Orgasms In Long-term Relationshipsmentioning
confidence: 88%
“…Simply put, sexy material that once was arousing becomes considerably less arousing over time. But, when men and women view novel sexual material-something new-they report feeling sexually aroused, and their genitals also show arousal (Both et al 2011;Dawson et al 2013;Over 1993, 2001;Meuwissen and Over 1990). Although there is evidence that both men and women habituate to sexual stimuli over time, a study by Both et al (2011) found that only women habituated to sexual stimuli (in this case a short erotic film), not men.…”
Section: Orgasms In Long-term Relationshipsmentioning
confidence: 89%
“…throughout each 270 s sexual stimulus so as to prevent habituation effects (Dawson, Lalumière, Allen, Vasey, & Suschinsky, 2013;. After each film, the participants were asked to rate the sexual intensity of the sexual activity depicted in the stimulus ("How sexually intense was the activity in the film?")…”
Section: Methodsmentioning
confidence: 99%
“…Studies of habituation to sexual stimuli in women and men demonstrate that genital [90][91][92][93][94][95][96] and subjective sexual arousal [90,91,[93][94][95][96] decline with repeated exposure to the same sexual stimulus, presumably because the hedonic quality associated with the stimulus changes as a function of repeated exposure. These studies also find that when novel stimuli are introduced, sexual arousal is restored [90][91][92][93][94][95][96]. Results from observational studies find a similar pattern; sexual desire can wane for both women and men in long-term relationships [56,57].…”
Section: Sexual Desire Across Timementioning
confidence: 98%